Investigating Species Composition and Abundance of Marine Microalgae from Temajo Island Waters, West Kalimantan, Indonesia - Safitri, Ikha; Kushadiwiojayanto, Arie Antasari; Sofiana, Mega Sari Juane; Nguyen, Duc-Hung; Adjout, Rebiha (Jurnal Biodjati, 2024)
Temajo Island is renowned for its marine tourism activities and is home to a range of organisms, including algae. Microalgae serve as indicator species, offering insights into the aquatic environment through their species composition and abundance. This study aims to provide preliminary data on the abundance and some ecological indices (diversity, evenness, and dominance) of microalgae on Temajo Island, which will be the basis for assessing water conditions and supporting conservation efforts and sustainable management of natural resources. The research was carried out at four stations with different characteristics. At each station, surface water samples were collected using a plankton net. The microalgae in these samples were subsequently examined under a microscope, and their quantities were measured. The microalgae abundance ranged from 2.84 to 7,697.14 ind/L, with an average of 193.34 ind/L. Chaetoceros was the most abundant genus, followed by Rhizosolenia, Guinardia, Thalassiosira, Pseudo-nitzschia, and Bacteriastrum. The diversity index (H’) ranged from 2.67 to 3.08, indicating moderate to high species richness, while the evenness index (E) ranged from 0.64 to 0.74, reflecting a high level of uniformity among microalgae populations. The dominance index (C) varied between 0.11 and 0.20, suggesting low dominance by any single genus. These indices collectively indicate a balanced and diverse microalgae community, underscoring the ecological health and stability of the Temajo Island waters. Preliminary information about the species composition and abundance of marine microalgae in this study provides valuable insights into the dynamics of microalgae populations and their ecological implications in the marine ecosystems of Indonesia.